2018
DOI: 10.1088/1361-6528/aaddc2
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap control of α-Fe2O3 nanozymes and their superior visible light promoted peroxidase-like catalytic activity

Abstract: Iron oxide nanoparticles (NPs) possessing peroxidase-like catalytic activity have been widely explored in recent decades, owing to their high stability against harsh conditions, low cost, flexibility in structure design and composition, adjustable activities and excellent biocompatibility in comparison with natural enzymes. Recently, a lot of great achievements have been made in this field of iron oxide nanozymes, however, this research has now reached a bottleneck in that the maximum activity enhancement is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Furthermore, hot electrons from plasmon-excited AuNPs promoted charge separation at the interface of Au/α-FeOOH, resulting in efficient cycling of Fe 3+ /Fe 2+ to produce Fenton reaction. The introduction of visible light has increased the POD-type activity of Fe 2 O 3 NPs by at least 1.2 times in the research of Zhu et al [ 275 ]. They found that the light-related catalytic property of Fe 2 O 3 nanozymes was concerned with the bandgap and light absorption range, which were responsible for the barrier density generation and the light energy absorption.…”
Section: Properties Of Metal- and Metal Oxide-based Nanozymesmentioning
confidence: 99%
“…Furthermore, hot electrons from plasmon-excited AuNPs promoted charge separation at the interface of Au/α-FeOOH, resulting in efficient cycling of Fe 3+ /Fe 2+ to produce Fenton reaction. The introduction of visible light has increased the POD-type activity of Fe 2 O 3 NPs by at least 1.2 times in the research of Zhu et al [ 275 ]. They found that the light-related catalytic property of Fe 2 O 3 nanozymes was concerned with the bandgap and light absorption range, which were responsible for the barrier density generation and the light energy absorption.…”
Section: Properties Of Metal- and Metal Oxide-based Nanozymesmentioning
confidence: 99%
“…Zhu et al regulated the pH value of the hydrothermal reaction system to change the morphology of Fe 2 O 3 NPs, which exhibited different bandgaps (1.78‐2.11 eV). Additionally, in comparison, the binding affinity and maximum reaction velocity of Fe 2 O 3 nanoflowers (1.78 eV) with TMB are at least 3.7 and 4.3 times higher than those of Fe 2 O 3 nanocubes (2.06 eV), respectively, which shows the catalytic performance can be specifically regulated by the crystal morphology with distinct crystallographic planes 61 . As shown in Figure 1A, Liu et al prepared Fe 3 O 4 nanocrystals with three diverse structures through similar hydrothermal reactions and further studied their POD‐like activities, which were structure‐dependent (in the order octahedra < triangular plates < cluster spheres) 77 .…”
Section: Activity Regulation Strategiesmentioning
confidence: 92%
“…The Fe 2 O 3 nanocrystals were obtained as previously reported . Typically, the Fe­(acac) 3 /PVP composite nanofibers were used as Fe 2 O 3 precursor and were prepared by electrospinning a homogeneous solution containing 0.4 g of PVP (Mw ≈ 1.3 × 10 6 ), 3.5 mL of acetic acid, 3 mL of ethanol, and 0.8 g Fe­(acac) 3 with a flow rate of 0.3 mL/h at 17.5 kV.…”
Section: Methodsmentioning
confidence: 99%